(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2018)
This article addresses the concepts of multiculturalism, interculturalism and intercultural education as theoretical perspectives to explain the intercultural dynamic of educational activities, and as epistemological challenges to indigenous knowledge in the school context. To examine these concepts we analyze the theoretical foundations which underlie them. We then formulate the epistemological problem of intercultural education, considering the context in which it takes place. Consequently, we argue that it is the dynamic of these concepts which makes it possible to consider interculturalism both in education and in the formulation of the questions posed by the intercultural situations under investigation.